Exploring the polymorphism of sofosbuvir via mechanochemistry: effect of milling jar geometry and material. Issue 11 (24th February 2022) - Chatziadi, Argyro; Skořepová, Eliška; Kohout, Martin; Ridvan, Luděk; Šoóš, Miroslav
Abstract : In this work, the influence of polypropylene jar properties on the polymorphic transformations of sofosbuvir during milling experiments is investigated. Abstract : Mechanochemistry has been used as a green and sustainable method to explore the polymorphism of several active pharmaceutical ingredients. Until now, many experimental conditions, such as the nature and amount of liquid additive, have been investigated to understand how they affect polymorphic transformations. However, the effect of the properties of the milling jar started to be explored only recently. Here, we extend our previous studies regarding the polymorphic transformations of sofosbuvir and perform new experiments in stainless steel and polypropylene jars. Interestingly, by comparing our results, we observe that not only the rate of transformation is faster in polypropylene jars but the conditions that are developed during the experiments favor the formation of a new form of sofosbuvir, not previously observed in stainless steel jar experiments. Analysis of the energetics of the system shows that these results are a consequence of the different geometry of the jars and of a significant rise in temperature due to the properties of the material. These findings are an important step toward understanding and even predicting how the choice of jar material affects the kinetics and polymorphic transformation of an active pharmaceutical ingredient during milling and, moreover, help designing the experiments according to the needs of the researcher.